Long-term stability of Pt/Ce0.8Me0.2O2-γ/Al2O3 (Me = Gd, Nb, Pr, and Zr) catalysts for steam reforming of methane. (26th April 2022) - Azevedo, Israel R.; da Silva, Andressa A.A.; Xing, Yutao T.; Rabelo-Neto, Raimundo C.; Luchters, Niels T.J.; Fletcher, Jack C.Q.; Noronha, Fabio B.; Mattos, Lisiane V.
Abstract: This study investigated the influence of dopants (Gd, Nb, Pr, and Zr) on the performance of Pt/Cex Me1-x O2-γ /Al2 O3 catalysts for the methane steam reforming (SRM) at 1073 K and at different space velocities. In-situ XRD, in-situ XANES, and Raman spectroscopy revealed the formation of a solid solution on the supports with Gd, Pr and Zr and an improvement in reducibility. No evidence of complete niobium inclusion into the ceria framework was observed and AlNbO4 and CeNbO4 phases were detected. All catalysts exhibited a severe initial deactivation, however, with Pt/CeNb/Al being most stable. Analyses of all spent catalysts revealed a negligible carbon deposition during the catalytic tests. TEM, XRD and N2 physisorption showed a collapse of the alumina structure and sintering of Pt particles as causing the early deactivation. The formation of segregated phases for Nb-doped ceria improved the thermal resistance of alumina and provided a closer contact with Pt crystallites, resulting in better stability. Graphical abstract: Image 1 Highlights: Solid solution (Cex Me1-x O2-γ ) was formed for Me = Gd, Pr, and Zr. Niobium exhibited a strong resistance to be inserted into the cerium framework. Incorporation of dopants promoted an enhancement of the properties of ceria. Pt sintering was considered as the main deactivation mechanism. Segregated phases of Niobium provided a better anchoring effect for Pt particles.